The Impact of Menstrual Cycle on Women's Athletic Performance: A Study on National Athletes of North Sumatra: A Study on Challenges and Opportunities - Nimrot Manalu; Ammalina Hudani; Helmina Ria Siregar; Ririn Irena Ririn Irena; Richa Putri Kinanti (Joska: Jurnal Isori Kampar, 2025)
Objectives: This research aims to investigate the relationship between menstrual cycle phases and athletic performance among elite female athletes from North Sumatra, Indonesia. The study specifically examines variations in strength, endurance, power, and technical skill execution across different phases of the menstrual cycle and identifies potential strategies for performance optimization. Methods: Thirty-eight elite female athletes (age 18-29 years) from various sporting disciplines participated in this 3-month longitudinal study. Performance metrics were assessed weekly and mapped to individual menstrual cycle phases confirmed through hormonal testing. Physical performance tests included countermovement jumps, 30m sprint, handgrip dynamometry, and sport-specific skill assessments. Participants completed daily symptom questionnaires and training logs. Statistical analysis employed repeated measures ANOVA, with post-hoc Bonferroni corrections and linear mixed models to account for individual variations. Results: Significant performance fluctuations were observed across menstrual cycle phases, with a 7.2% decrease in power output during the early luteal phase compared to the late follicular phase (p < 0.01). Endurance capacity decreased by 5.8% during the early follicular phase (p < 0.05). Technical skill execution demonstrated the highest variability (CV = 8.4%) during the premenstrual phase. Individual response patterns varied substantially, with 63% of athletes reporting performance decrements associated with specific cycle phases. Conclusion: The menstrual cycle significantly impacts various performance parameters in elite female athletes from North Sumatra, with the most pronounced effects during the early luteal and early follicular phases. Individual response patterns emphasize the need for personalized approaches to training periodization and competition scheduling. Implementation of cycle-based training modifications and symptom management strategies presents opportunities for performance enhancement.